Wavelet-based and database approach for locating faulty section of high impedance fault in a distribution system - Ali, Mohd Syukri; Bakar, Ab Halim Abu; Mokhlis, Hazlie; Arof, Hamzah; Illias, Hazlee Azil (PRZEGLĄD ELEKTROTECHNICZNY, 2013)
Locating a faulty section of the high impedance fault (HIF) in a power system network is a major challenge especially for a distribution network. This is due to the effect of the complexity of the distribution network such as branches, non-homogenous lines and high fault impedance that results in variation of fault locations. In this paper, analysis of fault locations using Discrete Wavelet Transform-based Multi-Resolution Analysis (MRA) has been proposed. A three-phase voltage signal measured at the main substation is analyzed to locate the high impedance fault. The 1st, 2nd and 3rd levels of detailed coefficient resolution for each phase were used for the classification of fault locations using the proposed method. The simulation was conducted on a 38-node distribution network system in a national grid in Malaysia using PSCAD software. The proposed method has successfully determined the actual fault location of a high impedance fault.